A survey on gastro-intestinal helminth parasites of Channa species at Kanchanrup Municipality, Saptari, Nepal - Shrestha, Jay Narayan; Thapa, Ganesh Bahadur; Shrestha, Samjhana (Journal of Natural History Museum, 2020)
A survey on gastro-intestinal helminth parasites of Channa species was done from the fish markets of Kanchanrup municipality and surrounding rivers and ponds with the help of local fishermen from May 2017 to April 2018. The experimental fishes were carried in the laboratory of Post Graduate Campus, Biratnagar. The visceral masses of the fishes were removed and examined under microscope by simple wet mount preparation for occurrence of various helminth parasites. Data were analyzed using SPSS version 16. C. orientalis (n=200) was infected by nematodes (Capillaria pterophylli), trematodes (Gonocerca physidis and Genarchopsis goppo) and cestodes (Senga sp.) giving prevalence of 87.5%. Similarly, C. striatus (n=225) was infected by nematodes (Camallanus intestinalis and Neocamellanus sp.), cestodes (Bothriocephalus sp.) and acanthacephalan (Pallisentis ophiocephali) with prevalence of infection 85.33%. The total multiple infection number was 131(74.9 %) found in C. orientalis. Channa spp. were heavily loaded by gastro-intestinal helminth parasites which may give rise to a health threat of zoonotic transmission to consumers. Therefore, immediate development of effective control measures and an application of good nourishment practice urgently needed to lower the helminth infection to fishes.